T. H. Green, Lectures on the Principles of Political Obligation and the Other Writings, ed. P. Harris — J. Morrow, 1986 - Adam Czarnota (Czasopismo Prawno-Historyczne)
Recenzja:  T. H. Green, Lectures on the Principles of Political Obligation and the Other Writings (ed. Paul Harris i John Morrow), Cambridge University Press, Cambridge 1986,